1986
DOI: 10.1111/j.1476-5381.1986.tb11189.x
|View full text |Cite
|
Sign up to set email alerts
|

A further search for selective antagonists at M2‐muscarinic receptors

Abstract: 1 In an attempt to obtain more selective antagonists acting at muscarinic M2-receptors, analogues of 4-diphenylacetoxy-N-methylpiperidine methobromide (4-DAMP methobromide) have been synthesized. These were tested, along with silabenzhexol, procyclidine, sila-procyclidine and AFDX-1 16, in dose-ratio experiments with guinea-pig isolated atria at 30'C and ileum at 30'C and 37°C. The agonist was carbachol and the selectivity was assessed from the difference between log K for receptors in ileum and log K for rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 7 publications
4
31
0
Order By: Relevance
“…AF-DX 116 appears to discriminate among the muscarinic receptor subclasses of the three tissues examined. These results are in agreement with those obtained both in whole-tissue pharmacology and in radioli gand-binding experiments, which indicate a marked preference of the drug for atrial mus carinic M2 receptors compared with those of smooth muscles [11,15,23,24], The signifi cant difference between the pA2 values of urinary bladder and atria found with AF-DX 116 further supports the heterogeneity of muscarinic receptors in peripheral effector organs, in agreement with previous results obtained in both tissue pharmacology [25] and binding studies [16,17,26]. In agree ment with these data, Angeli et al [27], by studying enantiomers of chiral muscarinic agonists, have shown that atrial receptors differ from bladder receptors.…”
Section: Discussionsupporting
confidence: 82%
“…AF-DX 116 appears to discriminate among the muscarinic receptor subclasses of the three tissues examined. These results are in agreement with those obtained both in whole-tissue pharmacology and in radioli gand-binding experiments, which indicate a marked preference of the drug for atrial mus carinic M2 receptors compared with those of smooth muscles [11,15,23,24], The signifi cant difference between the pA2 values of urinary bladder and atria found with AF-DX 116 further supports the heterogeneity of muscarinic receptors in peripheral effector organs, in agreement with previous results obtained in both tissue pharmacology [25] and binding studies [16,17,26]. In agree ment with these data, Angeli et al [27], by studying enantiomers of chiral muscarinic agonists, have shown that atrial receptors differ from bladder receptors.…”
Section: Discussionsupporting
confidence: 82%
“…The structural integrity of the muscarinic binding sites detected in transformants was assessed by determining the affinities of a series of muscarinic ligands in competition binding studies with [3H]-NMS. The ligands included two agonists (carbachol and oxotremorine), the non-selective antagonist atropine, and 3 selective antagonists (pirenzepine, 4-DAMP and methoctramine) which distinguish 3 subclasses of muscarinic binding sites in mammalian tissues [17][18][19]. The competition curves are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is an increase in affinity (more than obtained by replacing phenyl by cyclohexyl; Barlow & Shepherd, 1986), but there is a loss of selectivity. The very high selectivity of p-fluorohexahydro-sila-diphenidol can also be seen but the compound has relatively low affinity, less than that of silabenzhexol or silaprocyclidine (Barlow & Shepherd, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…There is an increase in affinity (more than obtained by replacing phenyl by cyclohexyl; Barlow & Shepherd, 1986), but there is a loss of selectivity. The very high selectivity of p-fluorohexahydro-sila-diphenidol can also be seen but the compound has relatively low affinity, less than that of silabenzhexol or silaprocyclidine (Barlow & Shepherd, 1986). The value for receptors in ileum (log K = 7.6) is comparable with that of diphenylhydroxymethyl-prop-3-ynyl-trimethyl-ammonium (log K = 7.3;Barlow et al, 1988), which has a C-CC-C chain instead of Si-C-C-C, but this compound has no selectivity (for atria log K = 7.4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation